إدارة الرياضة ومساهمتها في نجاح المؤسسة الإعلامية، دراسة ميدانية لإعلامي التلفزة الوطنية القسم الرياضي - لبلالطة, محمد رضا (My University, 2020)
بالعربية هدف الدراسة: التعرف على مدى تأثير إدارة الرياضية في تنويع التسيير واستغلال مختلف وظائفها داخل المؤسسة الإعلامية، وكذا التعرف على المبادئ أو العناصر التي يمكن الاعتماد عليها في نجاح المؤسسة الإعلامية بواسطة إدارة الرياضية بمختلف وظائفها. مشكلة الدراسة: هل تساهم إدارة الرياضية في نجاح المؤسسة الإعلامية؟ الفرضية العامة: تساهم إدارة الرياضة في نجاح المؤسسة الإعلامية الفرضيات الجزئية: -تساهم عملية التخطيط في نجاح المؤسسة الإعلامية. -تساهم عملية التنظيم في المؤسسة الإعلامية. -تساهم عملية التوجيه دور في نجاح المؤسسة الإعلامية. -تساهم عملية الرقابة في نجاح المؤسسة الإعلامية. عينة الدراسة: اعتمدنا في اختيارنا عينة الدراسة على أسلوب الحصر الشامل لجميع أفراد مجتمع الدراسة والبالغ عددهم 20 موظف وموظفة بالقسم الراضي للتلفزة الوطنية. المنهج: اعتمدنا على المنهج الوصفي لأنه المنهج المناسب لطبيعة هذا الموضوع الذي نحن بصدد دراسته. الأدوات المستعملة في الدراسة: اعتمدنا على استمارة الاستبيان كأداة لجمع البيانات. أهم النتائج المتوصل إليها: أظهرت نتائج الدراسة أن: - التخطيط يساهم في نجاح المؤسسة الإعلامية وهذا ما يتفق مع أهمية ومبادئ التخطيط. - التنظيم يساهم في نجاح المؤسسة الإعلامية وهذا ما يتفق عليه في وظيفة التنظيم في المجال الرياضي في الجانب النظري الذي يعتبر التنظيم في عملية الإدارية هو إطارها الخارجي ففي التنظيم تحديد المسؤوليات والسلطات التي تحدد المشرفين والمنفذين في مجموعة العلاقات الرسمية. - التوجيه يساهم ف نجاح المؤسسة الإعلامية وهذا ما يتفق عليه في وظيفة التوجيه في المجال الرياضي في الجانب النظري الذي يعتبر التوجيه في العمليات الإدارية هو إطارها الخارجي فالتوجيه، يحدد المسؤوليات والسلطات التي تحدد عمل المنفذين في مجموعة العلاقات الرسمية والغير رسمية. - أن الرقابة تساهم في نجاح المؤسسة الإعلامية. أهم الاقتراحات: - أن يتولى قيادة القطاعات التي لها علاقة بالمجال الرياضي كالمؤسسات الإعلامية متخصصون في مجال التسيير الإداري الرياضي. - اقتراح برنامج رقمني بين مختلف الوحدات لتسهيل عملية الأداء على مستوى الإدارة. - وضع خطط طويلة المدى على أن تقسم هذه الخطط إلى مراحل زمنية لضبط العمل أكثر. الكلمات المفتاحية: إدارة الرياضة، نجاح المؤسسة الإعلامية، التلفزة الوطنية، القسم الرياضي. The aim of the study: To identify the extent of the influence of the Sports Administration in diversifying the management and exploitation of its various functions within the media institution, as well as identifying the principles or elements that can be relied upon in the success of the media institution by the Sports Administration with its various functions. Study problem: Does the Sports Administration contribute to the success of the media institution? The general hypothesis: The Sports Administration contributes to the success of the media institution Partial assumptions: The planning process contributes to the success of the media organization. The organizing process contributes to the media institution. The mentoring process contributes to the success of the media organization. The oversight process contributes to the success of the media organization. The study sample: In our selection, we adopted the study sample on a comprehensive survey method for all members of the study population of 30 employees and employees in the content division of the National Television. The curriculum: We relied on the descriptive approach because it is the appropriate method for the nature of this subject that we are studying. Tools used in the study: We relied on the questionnaire as a tool to collect data. The study results showed that: Planning contributes to the success of the media organization and this is consistent with the importance and principles of planning. Regulation contributes to the success of the media organization, and this is what is agreed upon in the function of regulation in the sports field, in the theoretical side which regulates the organization in the administrative process as its external framework. -Guidance contributes to the success of the media organization, and this is agreed upon in the function of coaching in the sports field, in the theoretical aspect that guidance in administrative operations is its external framework. -Control contributes to the success of the media organization. Top suggestions: -To be in charge of leading sectors related to the sports field, such as media organizations, who specialize in sports management. -Propose a digital program between the various units to facilitate the performance process at the department level. -Developing long-term plans, provided that these plans are divided into time stages to control work more.
Keywords: إدارة الرياضة; نجاح المؤسسة الإعلامية; التلفزة الوطنية; القسم الرياضي